Implementasi etika bisnis syariah rumah makan ayam bakar wong solo cabang sa (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2019)
This study aims to determine whether there is an application of Islamic business ethics in the Ayam Bakar Wong Solo Samarinda. This type of research is a qualitative study that used descriptive analysis, which describes the data collected by researchers both from interviews and documentation during conducting research in the Ayam Bakar Wong Solo Samarinda. The results of this study indicate that business ethics carried out in general is in accordance with business ethics taught in Islam. Business ethics run by the restaurant can be seen from the way they work honestly, communicating kindly, straight to their pray, working hard in providing the best service, helping each other at work, maintaining punctuality, and helping others in need.